(untitled) (Journal of the Bangladesh Agricultural University, 2014)
Rita rita is an endangered riverine catfish having high market and nutritive values. The histological process of ovaries of Rita rita were performed to determine the breeding season for facilitating the artificial breeding in controlled environment. Fish were sampled monthly from the Brahmaputra River adjacent to Bangladesh Agricultural University (BAU), Mymensingh. The average Gonado-Somatic Index (GSI) ranged from 0.14 to 0.60 with the highest GSI value of 0.60 in July. The highest fecundity of 60114±3207.88 was found in the fish having length of 38.91±0.59 cm and weight of 1081.35±74.52 g. In contrast, the lowest fecundity was 37307.2±154.57 having length of 31.98±1.63 cm and weight of 810.87±49.75 g. The fecundity was found to increase with the increase of total length, body weight and the ovary weight and the relationship was linear and significant among them. Six developmental stages of ovaries were observed and categorized as the synchronous group. Vitellogenesis began in April with full development of ovaries in July. From this study, it can be presumed that gonadal development of R. rita peaked in July and breeding time within the months of June and July. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19938 J. Bangladesh Agril. Univ. 11(2): 341-348, 2013